The Role of RBC Oxidative Stress in Sickle Cell Disease: From the Molecular Basis to Pathologic Implications - Qinhong Wang; Rahima Zennadi (MDPI AG, 2021)
Sickle cell disease (SCD) is an inherited monogenic disorder and the most common severe hemoglobinopathy in the world. SCD is characterized by a point mutation in the β-globin gene, which results in hemoglobin (Hb) S production, leading to a variety of mechanistic and phenotypic changes within the sickle red blood cell (RBC). In SCD, the sickle RBCs are the root cause of the disease and they are a primary source of oxidative stress since sickle RBC redox state is compromised due to an imbalance between prooxidants and antioxidants. This imbalance in redox state is a result of a continuous production of reactive oxygen species (ROS) within the sickle RBC caused by the constant endogenous Hb autoxidation and NADPH oxidase activation, as well as by a deficiency in the antioxidant defense system. Accumulation of non-neutralized ROS within the sickle RBCs affects RBC membrane structure and function, leading to membrane integrity deficiency, low deformability, phosphatidylserine exposure, and release of micro-vesicles. These oxidative stress-associated RBC phenotypic modifications consequently evoke a myriad of physiological changes involved in multi-system manifestations. Thus, RBC oxidative stress in SCD can ultimately instigate major processes involved in organ damage. The critical role of the sickle RBC ROS production and its regulation in SCD pathophysiology are discussed here.